"Monogamy" in Primates: Variability, Trends, and Synthesis: Introduction to special issue on Primate Monogamy. Issue 3 (28th August 2015) - Díaz‐Muñoz, Samuel L.; Bales, Karen L.
Abstract : This paper is the introduction to a special issue on "'Monogamy' in Primates: Variability, Trends, and Synthesis." The term "monogamy" has undergone redefinition over the years, and is now generally understood to refer to certain social characteristics rather than to genetic monogamy. However, even the term "social monogamy" is used loosely to refer to species which exhibit a spectrum of social structures, mating patterns, and breeding systems. Papers in this volume address key issues including whether or not our definitions of monogamy should change in order to better represent the social and mating behaviors that characterize wild primates; whether or not primate groups traditionally considered monogamous are actually so (by any definition); ways in which captive studies can contribute to our understanding of monogamy; and what selective pressures might have driven the evolution of monogamous and non‐monogamous single female breeding systems. Am. J. Primatol. 78:283–287, 2016. © 2015 Wiley Periodicals, Inc.